Four‐Wave Mixing Response via Hybrid Coulomb‐Coupled Cavity Optomechanics. Issue 8 (24th June 2020) - Ullah, Muhib; Saif, Farhan; Wang, Li‐Gang
Abstract: The generation and manipulation of the four‐wave mixing (FWM) phenomenon is reported in a hybrid electrostatically Coulomb‐coupled optomechanical system as a result of light–matter interaction. The cavity is driven by a strong coherent pump and a weak probe field simultaneously in the presence of nanomechanical resonators (NMRs), and the output field can produce a new frequency component called the FWM frequency. In a hybrid Coulomb‐coupled cavity scheme, the existence of optomechanical coupling due to radiation pressure gives rise to the FWM phenomenon, which is shown both analytically and numerically. A controllable enhancement of the FWM intensity is found by tuning the pump field strength and its spectrum disappears upon switching the strength off. A significant enhancement in the FWM spectrum with two peaks is also predicted due to the Coulomb coupling strength existing between two electrostatically coupled NMR1 and NMR2 . A suppressive behavior of the FWM signal is also observed upon increasing the cavity decay rate and a substantial modulation in the signal by changing the probe‐pump field detuning. Finally, the FWM spectrum is very sensitive to both the effective resonance frequencies and effective masses of the NMRs. Abstract : The generation and manipulation of the four‐wave mixing (FWM) phenomenon is realized in a hybrid electrostatically Coulomb‐coupled optomechanical system. The system is driven by both a strong coherent pump and a weak probe field simultaneously, in the presence of nanomechanical resonators. The detailed properties of the FWM spectrum are discussed under different controllable parameters.